Study of PTC system with rectangular cavity receiver with different receiver tube shapes using oil, water and air - Rafiei, A. (MDPI AG, 2020)
Today, application of cavity receivers in solar concentrator systems is suggested as an interesting and novelty research subject for increasing thermal performance. In this research, a parabolic trough concentrator (PTC) with a rectangular cavity receiver was energetically investigated. The cavity receiver was studied with smooth and corrugated tubes. Different solar heat transfer fluids were considered, including water, air, and thermal oil. The effect of different operational parameters, as well as structural parameters, was investigated. The results showed that the linear rectangular cavity receiver with corrugated tube showed higher amounts of the absorbed heat and energy performance compared to the smooth tube as the cavity tube. Thermal performance of the rectangular cavity was improved using the application of water as the solar heat transfer fluid, which was followed by thermal oil and, finally, air, as the solar heat transfer fluid. Finally, it could be recommended that the rectangular cavity receiver with smooth tube using air as the solar heat transfer fluid is more appropriate for coupling this system with a Bryton cycle, whereas the rectangular cavity receiver with the corrugated tube using water or oil as the solar heat transfer fluid is recommended for achieving higher outlet temperature of the heat transfer fluid. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).